Work Ethic of Social Studies Teachers in the Implementation of Local Cultural Excellence of Tegal - Harini, Novi Dwi; Suyahmo, Suyahmo; Handoyo, Eko (JESS (Journal of Educational Social Studies), 2018)
Work ethic of social studies teachers will be able to make social studies learning effective so that it can create students who have good achievement in both education and society. In accordance with the nature of social studies (NCSS, 2000) social studies is an integrated study to incorporate the elements of local culture and civic education to make students become good citizens. The objective of this study is how the work ethic of social studies teachers of junior high schools in Tegal and investigate the implications of the work ethic of social studies teachers in the implementation of local cultural excellence on social studies learning. The method employed in this research was a qualitative method. The techniques of data collection were in-depth interviews, observation and document study. The study results show that the work ethic of junior high school teachers in Tegal has views on work, enthusiasm, and creativity which are affected by the social action background of social studies teachers of junior high schools, and it has implications and achievement of the urgency of social studies think global act local on the students.